Escape from Camp 14 : one man's remarkable odyssey from North Korea to freedom in the West - Harden, Blaine (New York : Viking, 2012)
Twenty-six years ago, Shin Dong-hyuk was born inside Camp 14, one of five sprawling political prisons in the mountains of North Korea. This is the gripping, terrifying story of his escape from this no-exit prison-- to freedom in South Korea.
Never heard the word "love" -- The boy who ate his mother's lunch -- School days -- The upper crust -- Mother tries to escape -- Mother tries to escape, version two -- This son of a bitch won't do -- The sun shines even on mouse holes -- Avoiding mother's eyes -- Reactionary son of a bitch -- Working man -- Napping on the farm -- Sewing and snitching -- Deciding not to snitch -- Preparing to run -- The fence -- Stealing -- Riding north -- The border -- China -- Asylum -- K'uredit k'adus -- South Koreans are not so interested -- U.S.A.
Includes bibliographical references.
Keywords: Sin, Tong-hyŏk, -- 1982-; Political prisoners -- Korea (North) -- Biography; Concentration camps -- Korea (North); Forced labor -- Korea (North); Korea (North) -- Social conditions